2014
DOI: 10.1364/oe.22.001008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optical ZP-OFDM transmission performance in multimode fiber links

Abstract: Abstract:In this paper, the performance of Zero Padding Orthogonal Frequency Division Multiplexing (ZP-OFDM) on intensity modulationdirect detection (IM-DD) multimode fiber (MMF) links is assessed by means of numerical simulations. The performance of ZP-OFDM is compared to classical Cyclic Prefixed form of OFDM (CP-OFDM) which is known to offer a limited performance in terms of symbol recovery in subcarriers suffering severe fading. Simulations results show that ZP-OFDM is able to reach 29 Gbps in 99.5% of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…2, where NVB is 8 and 12, respectively. It can be seen in both figures how the performance of the proposed data detection receivers for ZP-OFDM is improved respect to the use of the ZF receiver proposed in [4]. It is also shown that the combined OLA+V-BLAST receiver can achieve the performance of V-BLAST with low values of NVB.…”
Section: Simulation Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…2, where NVB is 8 and 12, respectively. It can be seen in both figures how the performance of the proposed data detection receivers for ZP-OFDM is improved respect to the use of the ZF receiver proposed in [4]. It is also shown that the combined OLA+V-BLAST receiver can achieve the performance of V-BLAST with low values of NVB.…”
Section: Simulation Resultsmentioning
confidence: 82%
“…The model employed in the numerical simulations defines a single 1550 nm wavelength unamplified intensity modulated and direct detected (IM-DD) optical MMF link and has been previously used to study optical OFDM [4] [9]. The transmitter models a directly modulated laser (DML) driven by a DMT signal limited in power to 5 dBm to prevent fiber nonlinearities.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations